Frame design and improvement of a small electric vehicle - Z. Wu; W. Pan; R. Niu; L. Liu (Mechanical Sciences)
The frame is a crucial component of a small electric vehicle. As the main body that bears the load, it has requirements for strength and deformation, meanwhile avoiding resonance with road excitation. Light-weighting of the frame can reduce vehicle cost while meeting performance requirements. This article designs a type of small electric vehicle frame, uses the CATIA 3D modeling software to model the frame entity, and then uses the ANSYS finite-element software to perform simulation analysis of the frame model, obtaining its deformation and stress conditions under the corresponding working conditions. Under the guarantee of frame safety, adjustments and optimizations of the frame dimensions are carried out, and their rationality is verified through simulation. Finally, the light-weighting of the structural design is achieved while meeting the requirements for strength and rigidity. The results show that the optimized frame meets the safety performance requirements and that the overall deformation and stress distribution are reasonable, ultimately achieving a weight reduction target of 10.7 % and realizing the light-weighting goal of the frame.